Farms Employing Foreign Workers in Italy: An Analysis with Census Micro Data - Silvia Coderoni; Concetta Cardillo; Maria Carmela Macri\`; Maria Angela Perito (German Journal of Agricultural Economics (GJAE), 2018)
Over the last decades, foreign workers have become a significant component of Italian agriculture workforce. Their presence and incidence are highly diversified with respect to farm typologies, type of contract and geographic location. A comprehensive representation of this complex phenomenon is thus the first step to understand the different problems and needs associated to the employment of foreign workforce. This study uses micro data from the 2010 Italian Agricultural Census to first describe what are the structural and geographical features of Italian farms employing foreign workers and then to group farms through a cluster analysis. Results give a detailed representation of the incidence of foreign workers employed, revealing which part of Italian agriculture relies more on foreign workers. The cluster analysis allows the definition of six groups: foreign workers are especially involved in livestock activities, both indoor and grazing and in farms specialized in permanent crops. Among major policy implications, analysing the presence of foreign workers can help targeting policies to agricultural production system needs.
Keywords: 330